Comparative Analysis of C9orf72 and Sporadic Disease in a Large Multicenter ALS Population: The Effect of Male Sex on Survival of C9orf72 Positive Patients - Trojsi, Francesca; Siciliano, Mattia; Femiano, Cinzia; Santangelo, Gabriella; Lunetta, Christian; Calvo, Andrea; Moglia, Cristina; Marinou, Kalliopi; Ticozzi, Nicola; Ferro, Christian; Scialò, Carlo; Sorarù, Gianni; et al. (Frontiers in Neuroscience, 2019)
We investigated whether the C9orf72 repeat expansion is associated with specific clinical features, comorbidities, and prognosis in patients with amyotrophic lateral sclerosis (ALS). A cohort of 1417 ALS patients, diagnosed between January 1, 2009 and December 31, 2013 by 13 Italian ALS Referral Centers, was screened for the C9orf72 repeat expansion, and the analyses were performed comparing patients carrying this expansion (ALS-C9Pos) to those negative for this and other explored ALS-related mutations (ALS without genetic mutations, ALSwoGM). Compared to the ALSwoGM group, ALS-C9Pos patients (n = 84) were younger at disease onset, at the first clinical observation and at diagnosis (p < 0.001). After correcting for these differences, we found that ALS-C9Pos patients had higher odds of bulbar onset, diagnosis of frontotemporal dementia (FTD) and family history of ALS, FTD, and Alzheimer's disease and had lower odds of spinal onset, non-invasive ventilation, hypertension and psychiatric diseases than ALSwoGM patients. Among these variables, those related to shorter survival time were: bulbar onset, presence of FTD, hypertension, psychiatric disease, and family history of ALS (p < 0.05). Cox proportional hazards regression multivariate analysis suggested that carrying the C9orf72 repeat expansion was an independent factor negatively impacting on survival time in men (HR 1.58, 95% CI 1.07–2.33, p = 0.021), but not in women (p > 0.05) as well as in the whole sample (p > 0.05). When compared to ALSwoGM, ALS-C9Pos showed an earlier disease onset, no significant diagnostic delay and a higher odds of bulbar onset, FTD and family history of ALS and dementia. Moreover, male sex drove the negative effect of expanded variant on survival, confirming the hypothesis that sex is likely to be a crucial factor in the biology of C9orf72-related disease.